Analysis of multiple-choice question (MCQ) of physics final examination in senior high school. (February 2020) - Rahmah, N; Yusrizal; Syukri, M
Abstract: This study aims to determine the quality of questions in multiple-choice test for School Final Exam of Physics subject at senior high school Pidie academic year 2018/2019, reviewed based on validity, reliability, level of difficulty, differentiating question level, and function of distracting questions. This non-experimental quantitative descriptive study involved year 12 students of there senior high school in Pidie academic year 2018/2019, namely senior high school Unggul Sigli, senior high school 1 Mila, and senior high school 1 Muara Tiga which were selected by stratified random sampling. The data source comes from the entire school final exam question sheet physics subjects for the 2018/2019 school year, answer keys and student answer sheets. The results of the package A and B final exam questions showed that not all of the questions were valid, the reliability of the questions was high, the differentiating question level was not the same, the difficulty level of the questions was different, and the effectiveness of the question was generally good and some of distracting questions need to be revised.